Assessing the hemodynamic contribution of capillaries, arterioles, and collateral arteries to vascular adaptations in arterial insufficiency. (20th October 2019) - Arciero, Julia; Lembcke, Lauren; Burch, Myson; Franko, Elizabeth; Unthank, Joseph
Abstract: Objective: There is currently a lack of clarity regarding which vascular segments contribute most significantly to flow compensation following a major arterial occlusion. This study uses hemodynamic principles and computational modeling to demonstrate the relative contributions of capillaries, arterioles, and collateral arteries at rest or exercise following an abrupt, total, and sustained femoral arterial occlusion. Methods: The vascular network of the simulated rat hindlimb is based on robust measurements of blood flow and pressure in healthy rats from exercise and training studies. The sensitivity of calf blood flow to acute or chronic vascular adaptations in distinct vessel segments is assessed. Results: The model demonstrates that decreasing the distal microcirculation resistance has almost no effect on flow compensation, while decreasing collateral arterial resistance is necessary to restore resting calf flow following occlusion. Full restoration of non‐occluded flow is predicted under resting conditions given all chronic adaptations, but only 75% of non‐occluded flow is restored under exercise conditions. Conclusion: This computational method establishes the hemodynamic significance of acute and chronic adaptations in the microvasculature and collateral arteries under rest and exercise conditions. Regardless of the metabolic level being simulated, this study consistently shows the dominating significance of collateral vessels following an occlusion.